Pengaruh Pengendalian Intern Kas Terhadap Efektivitas Pengelolaan Kas Pada Senyum Media Stasionery Di Jember - Jessica Shandy Darmadji; Diana Dwi Astuti; Lia Rachmawati (Institut Teknologi dan Sains Mandala, 2022)
ABSTRACT This study aims to examine the effect of internal cash control on the effectiveness of cash management at Smile Media Stationery Jember. The independent variables used include: Control Environment (X1), Risk Assessment (X2), Information Systems (X3), Control Procedures (X4), Control Monitoring (X5). The dependent variable is Cash Management Effectiveness (Y). This research uses quantitative descriptive analysis with a case study approach. The population used in this study were all employees of Smile Media Stationery Jember, amounting to 80 people. The sample in this study were 33 employees of Smile Media Stationery Jember who were selected through purposive sampling method. The data collection method used in this study is primary data using questionnaires, interviews, observations and literature studies. The data analysis method used is multiple linear regression analysis, F test, t test, and coefficient of determination, with data quality tests through validity and reliability tests. The results of the analysis show that simultaneously, all independent variables have an influence on the effectiveness of cash management. Meanwhile, it is partially known that the control environment is the only variable that has a significant influence on the effectiveness of cash management.